การกำจัดก๊าซไฮโดรเจนซัลไฟด์โดยเครื่องกรองชีวภาพ - ณัฐพล รัตนมุขย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objective of this research was to study the removal of hydrogen sulfide by a composite media biofilter. The study involved two stages. The first stage was to optimize media in the removal of hydrogen sulfide by comparing the removal efficiency of four main media comprising compost, bamboo fluff soil, lava rock and activated carbon. The sludge from municipal wastewater treatment plant served as a source of microorganisms. Cow manure was used as a source of nutrients and coconut shell was used to prevent bed compaction. The ratio of main media : coconut shell : sludge : manure was 60:20:10:10 by volume. This experiment varied the empty bed residence time at 45, 60 and 75 seconds and hydrogen sulfide concentration ranged from 50-300 ppmv. The second stage used with main media from first stage to examine the influence of gas flow direction on the removal efficiency by comparing the removal efficiency between bottom-load biofilter and top-load biofilter. The second stage varied the empty bed residence time at 25, 50 and 75 seconds and hydrogen sulfide concentration was 300 ppmv. This result showed that the compost media having height of packed bed 1 meter, hydrogen sulfide concentration of 300 ppmv. empty bed residence time was 45 seconds can achieve the removal efficiency 100%. However, bamboo fluff soil, lava rock and activated carbon needed height of packed bed more than 1.25 meter. Compost, bamboo fluff soil, lava rock and activated carbon achieved the maximum elimination capacity of 122, 111, 72 and 108 g/m[superscript 3]-hr. The pressure drop were 20, 11, 9 and 25 mm. H[subscript 2]O/meter of bed, repectively. The compost has highest elimination capacity. It is a suitable media for the removal of hydrogen sulfide by biofilter. The second experiment revealed that the top-load biofilter had removal efficiency similar to bottom-load biofillter at the empty bed residence time at least 50 seconds. For empty bed residence time 25 second the removal efficiency of top-load biofilter was less than the removal efficiency of bottom-load biofilter.